Electromagnetic ELM and inter-ELM filaments detected in the COMPASS Scrape-Off Layer. (August 2017) - Spolaore, M.; Kovařík, K.; Stöckel, J.; Adamek, J.; Dejarnac, R.; Ďuran, I.; Komm, M.; Markovic, T.; Martines, E.; Panek, R.; Seidl, J.; Vianello, N.; et al.
Highlights: The fine structure of ELM and inter-ELM filaments was detected in the SOL region of the COMPASS tokamak. ELM events are constituted by multiple fragmented filamentary electromagnetic (EM) filaments. The U-probe concept insertable probe allowed the direct evaluation of ELM and inter-ELM EM properties. A direct measure of the B parallel current density inside ELM and inter-ELM filament is provided. Abstract: In fusion devices strong interest is deserved to the edge filament transport both related to turbulent and ELMy structures, because they are believed to provide important interaction with the plasma facing components and divertor plates. Among their features also the electromagnetic (EM) properties are expected to play an important role and in particular for the high beta regimes expected in future devices. The presence of ELM and inter-ELM electromagnetic filaments were detected during H-mode discharges in COMPASS device Scrape-Off Layer, where a new probe head was recently developed and commissioned. The diagnostic allows the simultaneous measurements of electrostatic and magnetic fluctuations with high time resolution, suitable for the identification of EM features of filaments. The method allows in particular the direct measurement of the current density associated to filaments. Detailed electrostatic and electromagnetic features analysis revealed a complex and fragmented structure within a single ELM and strong peaks in parallel current density Jtor are observed to characterize the ELM bunch. Analogous EM structures are observed also in inter-ELM phase, but with more than one order of magnitude lower intensity and time scale.